The Effect of Lawi-Lawi Grass (Caulerpa racemosa) on Blood Glucose Levels of Rattus norvegicus - Irviani Anwar Ibrahim; Nur Ainin Alfi; Syahrul Basri (Window of Health : Jurnal Kesehatan, 2025)
Lawi-lawi seaweed (Caulerpa racemosa) contains fibre and antioxidants, which are the largest components that can inhibit blood clotting and reduce blood sugar levels by slowing the release of glucose into the blood. This study aimed to determine the effect of giving Lawi-lawi seaweed (Caulerpa racemosa) on the blood glucose levels of male Wistar strain Rattus norvegicus. This research is pure experimental research, using a posttest-only control group design. The sample consisted of 25 male white rats weighing 150-200 grams. All rats were coded and then induced with alloxan at a dose of 130 mg/kg BW, if the rat's blood glucose level was > 200 then the rat was said to be diabetic, then the rats were randomly divided into 5 groups, negative control, positive control, treatment 1 (1.87g), treatment 2 (3.75g) and treatment 3 (5.62g) groups. The results of the post hoc test on the average change in blood glucose levels of rats for 30 days of treatment generally showed a value of p = 0.000, where p <0.05 so that it could be interpreted that between the negative control group receiving standard feed treatment, the positive control group being given metformin, There were differences in changes in blood glucose levels in the treatment groups of seaweed at doses 1, 2 and 3 doses, meaning that there was an effect between the groups giving Lawi-lawi seaweed on reducing blood glucose levels of rats for 30 days of treatment.